Pemodelan matematika pengeringan apel serut dengan perlakuan blansing dan non blansing berbasis energi surya - Siti Asmaniyah Mardiyani; Dwi Susilowati Susilowati; Efendi S Wirateruna (AGROINTEK, 2024)
A drying technique utilizing solar energy on shredded apples as raw material for apple infusion has a reduced emission risk while also producing high-quality drying products.This study aimed to determine the optimum semi-theoretical mathematical model for drying shredded apples after blanching and non-blanching treatments utilizing three simple mathematical models: Newton, Henderson, Pabis, and Page. The results showed that blanched shredded apples dried using the Convective Solar Drying (CSD) method had the highest rate of decrease in the moisture ratio compared to those dried in the open sun drying (OSD). The three semi-theoretical models examined can be used to forecast the rate of decline in the water content ratio of dry shaved apples in all treatment combinations, as demonstrated by a value of R2 more than 0.9. Based on a comparison of the validity of each semi-theoretical model utilized, Page's model is the best model for characterizing the drying kinetics of shredded apples for both blanching CSD, non-blanching CSD, blanching OSD, and non-blanching OSD drying. The information acquired will be important in selecting an appropriate apple pretreatment handle and drying model for shredded apples.